La Chimica industriale e applicata nella Facoltà di Ingegneria dell’Università di Palermo dalle origini al 1923 - Silvestri, Giuseppe (Chimica nella Scuola, 2023)
This insight on the first part of the pathway which led to the widening of the presence of disciplines dealing with applied and industrial Chemistry starts, in 1834, with the institution of the teaching of Chemistry applied to arts and trades and arrives, in 1923, to the stabilization of the school of application for engineers, as institution with legal and administrative autonomy, as premise to the Faculty of Engineering and then to the degree in chemical Engineering.